PENGARUH TIME PRESSURE, KOMPLEKSITAS TUGAS, DAN AUDIT BERKELANJUTAN TERHADAP INDEPENDENSI AUDITOR DENGAN FEE AUDIT SEBAGAI VARIABEL MODERATING (STUDY EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI SURABAYA) - Habibah, Ulfa Nur; Widiastoeti, Hendy (Universitas 17 Agustus 1945 Surabaya, 2018)
ABSTRACTThis study aims to test empirically the Effects of Time Pressure, Task Complexity and Sustainable Audit Independence Against Auditor with the Audit Fee as Moderating Variable. Auditor independence has a very important role to the auditor when executing the audit assignment which is to preserve fairness, and no partiality to anyone. The population in this study is the auditor who works at KAP Surabaya consisting of 43 KAP. Sampling is used in a way Simple random sampling (simple random sample). Questionnaires were distributed to respondents as many as 80 and the number of questionnaires that can be analyzed as many as 55. The data analysis technique used in this study is a PLS (Partial Least Square) with SmartPLS application version 2.0 M3. The results of this study indicate that the time pressure significantly affect the independence of the auditor, the audit sustained significantly affect the independence of the auditor, fee audits significantly affect the independence of the auditor, Time pressure is moderated by a fee audit significantly affect the independence of the auditor, the audit sustained moderated by audit fees significantly affect the auditor's independence, while the complexity of the task does not significantly influence the independence of auditors and the complexity of the task to be moderated by the audit fee no significant effect on the independence of auditors. Keywords: time pressure, task complexity, continuous auditing, audit fees, auditor independence